A study of spectrum and fetomaternal outcome of Jaundice in pregnant women: an experience from a tertiary referral centre of North India - Agrawal, Monica; Bhanu, Meenakshi; Sankhwar, Pushpa Lata; Deo, Sujata; Jaiswar, S. P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy in jaundice is an important Medical disorder, commonly seen in developing countries like India. The objective of the study was to evaluate the causes leading to jaundice in pregnancy and to analyse the feto-maternal outcome in patients of jaundice in pregnancy. Methods: This was a prospective observational study of antenatal cases with jaundice admitted in the Department of Obstetrics and Gynecology, King Georges Medical University, Lucknow over a period of one year after getting approval of ethical clearance. Total 122 cases were enrolled after informed consent. Results: Total of 122 cases were enrolled, Incidence of jaundice in pregnancy was 1.2%. Majority of patients were of age group 20-25 years 48.4%. About 69.7% presented at gestational age of 29-40 weeks. Most common cause was pre-eclampsia 33.6%, followed by cholestasis 23.75% and hepatitis 17.2%. Amongst hepatitis, most common was hepatitis B in 26.7%. Out of 122 cases, 59.8% delivered while 50.2% were undelivered 52.4% patients improved and were discharged while 47.6% patients expired. Vaginal deliveries were 56.1%, abdominal deliveries were 43.9%, and main reason for maternal mortality was hepatic encephalopathy in 64.6%. Mortality was higher in patients with total bilirubin > 10mg%. Perinatal mortality was 37%. Conclusions: Pregnancy complicated with jaundice carries very poor maternal and fetal outcome. Poor outcome may be attributed to delay in seeking medical advice, lack of awareness, lack of proper antenatal checkups 100% ANC booking can help in reducing fetomaternal morbidity and mortality.